2015
DOI: 10.1021/cg501865h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition of Steroid Hormones in the Solid State: Stark Differences in Cocrystallization of β-Estradiol and Estrone

Abstract: While the understanding of the supramolecular chemistry of steroidal hormones is largely based on receptor binding studies in vitro and in vivo, their solid-state molecular recognition properties remain unexplored. Here, we use mechanochemical cocrystallization and single crystal X-ray structure analysis to gain insight into the solid-state complexation of sex hormones with arenes, by systematic investigation of the ability of two important estrogens ß-estradiol (bes) and estrone (est) to form cocrystals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 140 publications
0
19
0
Order By: Relevance
“…39,40 The extension to co-crystallization with larger molecules has been partially in-vestigated, with cocrystals with isonicotinamide (ULUFIS) and piperazine dihydrate (ULUFOY) being reported from a search for increased solubility, 41 and with pyrene (CUTBEZ), phenanthrene (RUGYID), benzo[h]quinoline (RUFYIC) and 1,2-dimethylnapthalene (RUFOY) in investigations of the molecular recognition of steroids. 42,43 The crystal energy landscape ( Fig. 7) suggests that other polymorphs of BES are highly likely, although Form I may well be the most thermodynamically stable form given the accuracy of the calculations.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 The extension to co-crystallization with larger molecules has been partially in-vestigated, with cocrystals with isonicotinamide (ULUFIS) and piperazine dihydrate (ULUFOY) being reported from a search for increased solubility, 41 and with pyrene (CUTBEZ), phenanthrene (RUGYID), benzo[h]quinoline (RUFYIC) and 1,2-dimethylnapthalene (RUFOY) in investigations of the molecular recognition of steroids. 42,43 The crystal energy landscape ( Fig. 7) suggests that other polymorphs of BES are highly likely, although Form I may well be the most thermodynamically stable form given the accuracy of the calculations.…”
Section: Discussionmentioning
confidence: 99%
“…André, in collaboration with Friščić´s team, disclosed novel cocrystals of ß-estradiol and estrone with 1,2-dimethylnaphthalene, phenanthrene, anthracene, 9,10-anthraquinone, phenanthridine, benzo[h]quinoline, and perfluoronaphthalene [ 57 ]. Knowledge of the molecular recognition and complexation of steroids was already an established area of research, and solid-state chemistry, along with crystal engineering, had recently been proposed to explore their molecular recognition properties[ 58 ].…”
Section: Developments Of Mechanochemistry In Portugalmentioning
confidence: 99%
“…A subsequent study focusing on cocrystals of β-estradiol established that cocrystallization is not based on a particular type of steroid-arene interaction, but on the assembly of a square-grid hydrogen-bonded β-estradiol host templated exclusively by arene molecules of a specific size. 91 Mechanochemical cocrystallization screening was also utilized to elucidate which elements of a molecular structure are relevant for a small molecule to act as a template for the assembly of different hydrogen-bonded hosts based on caffeine and succinic acid (Figure 7 a). 73 A screen of a small library of 16 potential guest molecules based on differently substituted methane derivatives revealed that the formation of a host framework takes place only if the size of the potential guest lies between 3.5 Å and 3.8 Å (Figure 7 a).…”
Section: Syn Lettmentioning
confidence: 99%